Search Engine Programming in JavaScript for Digital Dictionaries - Krohn, Haakon Stensrud (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In this paper, aimed at lexicographers without previous knowledge about program- ming, we explain, step by step, how to program search engines with different functiona- lities in JavaScript for digital dictionaries. In this way, we expect to contribute to lexico graphers to participate more actively in the development of this tool so essential for a dictionary. The examples are based on characteristics of the search engines of several dictionaries available on the web and focus mainly on three types of correspondences between the search term and the keywords: complete, partial and with wildcard. Also shown is how to create an additional function to allow even more flexibility by means of character substitution